UNDERSTANDING SENTENCE STRUCTURE: MAIN, SECONDARY AND PERIPHERAL ELEMENTS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the theory of parts of the sentence, focusing on theirclassification into primary, secondary, and tertiary components. It provides an overview ofthe principles underlying these categories, emphasizing their functional roles in sentencestructure. Special attention is given to secondary parts, such as objects, attributes, andadverbial modifiers, which enhance the basic subject-predicate framework. The discussionalso addresses the challenges associated with tertiary parts, including their definition, contextual variability, and overlap with pragmatics. The article concludes by highlightingthe importance of this theory in understanding the complexity and adaptability of langu